Webtoon based e-comic the material of my dear earth my poor earth the content of IPAS grade V elementary school - Nurjanah, Amelia; Yasa, Arnelia Dwi; Triwahyudianto, Triwahyudianto (Jurnal Bidang Pendidikan Dasar, 2024)
The development of science and technology is challenge for educators to continue create new innovations in learning process. The purpose of this research is develop and produce Webtoon based E-Comic that is feasible medium for learning IPAS on the material my dear earth my poor earth grade V elementary school. The research model in this study uses the 4D, namely: Define, Design, Develop, Disseminate. The subjects in this study were material experts, linguists, media experts, teachers and students. The results feasibility analysis based on experts obtained 91% in very good category, the practicality analysis obtained 89% in very practical category, and the effectiveness analysis obtained an average of 95% in very effective category. Based on the results, the Webtoon based E-Comic learning media on the material my dear earth my poor earth IPAS content that has been developed using the 4D model is very feasible to use.